2022
DOI: 10.3390/ijms23137280
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Plays Central Role in Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a global pandemic that affects one-quarter of the world’s population. NAFLD includes a spectrum of progressive liver disease from steatosis to nonalcoholic steatohepatitis (NASH), fibrosis, and cirrhosis and can be complicated by hepatocellular carcinoma. It is strongly associated with metabolic syndromes, obesity, and type 2 diabetes, and it has been shown that metabolic dysregulation is central to its pathogenesis. Recently, it has been suggested that metabolic- (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 209 publications
1
36
0
Order By: Relevance
“…Mitochondrial dysfunction has been linked to a reduction in fatty acid β-oxidation (FAO) that is due to decreased carnitine palmitoyl transferase-1 (CPT-1) activity and decreased fatty acid clearance, resulting in the pathogenesis of NAFL. 295 Moreover, impaired hepatic FAO is related to the progression of NAFLD in patients with obesity. During NAFLD, the impairment of FAO inhibits the activity of PPARα, resulting in hepatic lipid accumulation and inflammation.…”
Section: Pathogenic and Regulatory Mechanisms Of Aging-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction has been linked to a reduction in fatty acid β-oxidation (FAO) that is due to decreased carnitine palmitoyl transferase-1 (CPT-1) activity and decreased fatty acid clearance, resulting in the pathogenesis of NAFL. 295 Moreover, impaired hepatic FAO is related to the progression of NAFLD in patients with obesity. During NAFLD, the impairment of FAO inhibits the activity of PPARα, resulting in hepatic lipid accumulation and inflammation.…”
Section: Pathogenic and Regulatory Mechanisms Of Aging-related Diseasesmentioning
confidence: 99%
“…With aging, impairment of hepatic autophagy in the fatty liver may fail to remove damaged mitochondria, therefore leading to activation of the mitochondrial death pathway and causing NASH via oxidative stress and apoptosis. 295 In general, the liver has a remarkable capacity for regeneration and restoration. However, age-mediated changes impair the hepatic regenerative capacity.…”
Section: Pathogenic and Regulatory Mechanisms Of Aging-related Diseasesmentioning
confidence: 99%
“…NAFLD has emerged as the most prevalent chronic liver disease. Consisting of steatotic nonalcoholic fatty liver (NAFL) in its earlier phase and inflammatory nonalcoholic steatohepatitis (NASH) as a late-stage exacerbation, this major pandemic currently affects close to 30 % of the global population [2,3]. In addition, NAFLD is a leading cause of HCC [4], with NASH being the foremost risk factor for developing this type of cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that mitochondrial dysfunction plays a significant role in the development of MAFLD. The oxidative damage of mitochondrial fatty acids and the decline of mitochondrial quality are considered to be extremely important motivations in the development of MAFLD[ 5 ]. Thus, modulation of mitochondrial function may be an effective strategy to alleviate MAFLD.…”
Section: Introductionmentioning
confidence: 99%